Tundra be dammed: Beaver colonization of the Arctic. (25th June 2018) - Tape, Ken D.; Jones, Benjamin M.; Arp, Christopher D.; Nitze, Ingmar; Grosse, Guido
Abstract: Increasing air temperatures are changing the arctic tundra biome. Permafrost is thawing, snow duration is decreasing, shrub vegetation is proliferating, and boreal wildlife is encroaching. Here we present evidence of the recent range expansion of North American beaver ( Castor canadensis ) into the Arctic, and consider how this ecosystem engineer might reshape the landscape, biodiversity, and ecosystem processes. We developed a remote sensing approach that maps formation and disappearance of ponds associated with beaver activity. Since 1999, 56 new beaver pond complexes were identified, indicating that beavers are colonizing a predominantly tundra region (18, 293 km 2 ) of northwest Alaska. It is unclear how improved tundra stream habitat, population rebound following overtrapping for furs, or other factors are contributing to beaver range expansion. We discuss rates and likely routes of tundra beaver colonization, as well as effects on permafrost, stream ice regimes, and freshwater and riparian habitat. Beaver ponds and associated hydrologic changes are thawing permafrost. Pond formation increases winter water temperatures in the pond and downstream, likely creating new and more varied aquatic habitat, but specific biological implications are unknown. Beavers create dynamic wetlands and are agents of disturbance that may enhance ecosystem responses to warming in the Arctic. Abstract : We present evidence of the recent range expansion of North American beaver ( Castor canadensis ) into the Arctic, and consider how this ecosystem engineer might reshape the landscape, biodiversity, and ecosystem processes. We developed a remote sensing approach that maps formation and disappearance of ponds associated with beaver activity, and showed that since 1999 beavers have colonized a predominantly tundra region (18, 293 km 2 ) of northwest Alaska. Beaver colonization of tundra streams triggers permafrost thaw and has important biological implications for freshwater ecosystems.